STUDI INDIGENOUS: KONSEP PUNISHMENT DALAM RELASI GURU DAN SISWA SMA - Utami, Meyliza Nafisah; Adri, Zakwan (CAUSALITA : Journal of Psychology, 2024)
Education and humans cannot be separated in life because education can create a skilled, intelligent and qualified young generation. Education has a role in improving human resources and is one of the efforts to realize a cultural heritage from one generation to another through learning. The quality of education in Indonesia is still experiencing problems and is often discussed by experts. In one of the provinces in Indonesia, namely West Sumatra, it can be found that the conditions for high school learning activities are not yet optimal. This is because the quality of learning outcomes in class is still above average and has not yet reached maximum results. In the learning process, there are learning methods that can make students interact with each other, one of which is the punishment method, where this learning method will make teachers and students interact with each other. Punishment is an effort made by teachers to improve and direct students in a better direction with the hope of changing and motivating students so that they avoid existing punishments. This research aims to examine the dynamics of the concept of punishment in the relationship between teachers and students. The use of qualitative methods in this research is used because this research applies an indigenous study of the dynamics of the concept of punishment in the relationship between teachers and students. The research was conducted using observation, interviews and documentation on 430 class XI high school students in Bukittinggi City. The results of this research show that the punishment given to high school students in teacher-student relationships can take the form of physical punishment, verbal punishment, punishment involving activities, academic punishment, group punishment, and emotional punishment. The psychological impacts experienced by high school students after receiving punishment from their teachers include hating their teachers, feeling embarrassed, lacking self-confidence, hurting or affecting students' mental health, feeling tired, and feeling burdened.